Multicultural Based Inclusive Islamic Education Model in Schools - Hosnan Hosnan (Indonesian Journal of Education and Social Studies, 2022)
This study aims to analyze the multicultural-based inclusive Islamic education model conducted at an educational institution in Probolinggo Regency, East Java. This research method is a case study type qualitative research. Informants in this study consisted of school principals, vice principals, and teachers. The results show that the multicultural-based inclusive Islamic education model applies; first, the Islamic Education Curriculum is oriented towards Inclusive-Multicultural education to internalize multicultural education so that an awareness of maintaining social cohesiveness is born and sharpening self, social and cultural wisdom. Second, the Epistemological Transformation Paradigm of National Education can be applied and conforms to the principles of national education administration. Based on the research results, strengthening multicultural-based inclusive Islamic education can be implemented at all levels of educational institutions.